Consulting Committee/Contents - ad-bsj, ad-bsj; Abdulnabi Abdulmajeed , Prof. Dr. Mariam (Basra studies journal, 2026)
Aspecific Refered Journal Published by the center of Basra Studies &Arab Gulf Basrah University